The Implementation Of Management And Methods Of Tahfiz Al Qur'an In Ma As Surkati And Man Salatiga: Implementasi Manajemen Dan Metode Tahfiz Al Qur’an Di Ma As Surkati Dan Man Salatiga - Joko Prasetiyo; Mukh Nursikin (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
Implementation of management and tahfiz al Qur'an methods at MA As Surkati and MAN Salatiga This research aims to find out how the management and methods of tahfiz al Qur'an are implemented at MA As Surkati and MAN Salatiga, the supporting and inhibiting factors, as well as the similarities and differences between tahfiz al Qur'an in the two madrasas. The method used in this research is a descriptive qualitative method with a comparative study type of research. Data collection techniques use observation, interviews and documentation methods. Stages in data analysis through data reduction, data presentation and drawing conclusions. The research results show that the implementation of tahfiz al-Qur'an management at MA As Surkati and MAN Salatiga consists of four parts, namely planning, organizing, implementing and evaluating. The method used in tahfidz al-Qur'an is the takrir method at MAN Salatiga and takrir plus translation at MA As Surkati. Among the supporting factors for tahfiz al-Qur'an in both madrasas are intention and determination, intelligence and enthusiasm, discipline and consistency, persistent and patient teachers, a good environment, repeating, staying away from sin, motivation and guidance, rewards and punishments and prayer. The inhibiting factors include internal factors within students such as feeling lazy and bored, as well as external factors such as a poor environment. The similarities between the tahfiz al Qur'an program at MA As Surkati and MAN Salatiga are the target of memorizing 30 juz, student acceptance tests, free memorization methods, evaluation exams using the tasmi' method, giving rewards and punishments and involving parents in order to support students. The differences between the tahfiz programs in the two madrasas lie in the students participating in the program, the period of education, the existing tahfiz program model, evaluation, and the levels of rewards and punishments